Analysis of Different Types of Network Attacks on the GNS3 Platform - Das, Resul; Bitikçi, Burak (My University, 2020)
In this study, DDoS, SQL injection and XSS attacks that hackers use most in cyber attacks are modeled on GNS3emulator platform and network security is analyzed. A network scenario was designed using Graphical NetworkSimulator (GNS3), virtual machines, VMware workstation, firewall, router, and switches in order to examine theattacks on networks in real environment. Attacks were performed on this network with different techniques andtarget servers and devices were affected by the attacks. At the time of the attack, network traffic between theattacker and the target device was recorded with Wireshark software. Network traffic records and traces wereexamined and evaluations of attacks were made.
Keywords: Bilgisayar Bilimleri; Yazılım Mühendisliği